2019
DOI: 10.3390/ijms20204990
|View full text |Cite
|
Sign up to set email alerts
|

Solid Nanocrystals of Rebamipide Promote Recovery from Indomethacin-Induced Gastrointestinal Bleeding

Abstract: Indomethacin (IMC)-induced gastrointestinal (GI) injuries are more common in rheumatoid arthritis (RA) patients than in other IMC users, and the overexpression of nitric oxide (NO) via inducible NO synthase (iNOS) is related to the seriousness of IMC-induced GI injuries. However, sufficient strategies to prevent IMC-induced GI injuries have not yet been established. In this study, we designed dispersions of rebamipide (RBM) solid nanocrystals (particle size: 30–190 nm) by a bead mill method (RBM-NDs), and inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…On the other hand, no intestinal lesions were detected in the rats treated with MLX-NPs, and there were fewer gastric lesions in rats treated with MLX-NPs than in rats administered MLX-TDs (P < 0.05). Previous studies have reported that NSAIDs inhibit cyclooxygenase and cause the depletion of endogenous prostaglandins (PG), resulting in the formation of gastric lesions [39][40][41]. In addition, the direct stimulation by NSAIDs in the stomach and small intestine induces the overexpression of neutrophils, the formation of nitric oxide (NO) via inducible NO synthase, and these changes in the levels of neutrophils, NO and prostaglandins cause the pathogenesis of intestinal ulceration [39][40][41].…”
Section: Usefulness Of Oral Formulations Of MLX Solid Nanoparticles As Therapy For Ra Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, no intestinal lesions were detected in the rats treated with MLX-NPs, and there were fewer gastric lesions in rats treated with MLX-NPs than in rats administered MLX-TDs (P < 0.05). Previous studies have reported that NSAIDs inhibit cyclooxygenase and cause the depletion of endogenous prostaglandins (PG), resulting in the formation of gastric lesions [39][40][41]. In addition, the direct stimulation by NSAIDs in the stomach and small intestine induces the overexpression of neutrophils, the formation of nitric oxide (NO) via inducible NO synthase, and these changes in the levels of neutrophils, NO and prostaglandins cause the pathogenesis of intestinal ulceration [39][40][41].…”
Section: Usefulness Of Oral Formulations Of MLX Solid Nanoparticles As Therapy For Ra Patientsmentioning
confidence: 99%
“…Previous studies have reported that NSAIDs inhibit cyclooxygenase and cause the depletion of endogenous prostaglandins (PG), resulting in the formation of gastric lesions [39][40][41]. In addition, the direct stimulation by NSAIDs in the stomach and small intestine induces the overexpression of neutrophils, the formation of nitric oxide (NO) via inducible NO synthase, and these changes in the levels of neutrophils, NO and prostaglandins cause the pathogenesis of intestinal ulceration [39][40][41]. Taken together, the data suggest decreasing the MLX dosage (the amount administered orally) by improving BA attenuates the direct stimulation by MLX in the stomach and small intestine, resulting in a decrease in the onset of gastrointestinal lesions.…”
Section: Usefulness Of Oral Formulations Of MLX Solid Nanoparticles As Therapy For Ra Patientsmentioning
confidence: 99%
“…3 ). Our previous study showed that gastrointestinal injuries caused by IMC were similar in normal and sham-operated rats [ 9 ]. Analysis of the lesion area showed a significant decrease in the disability rate in the TEP-treated AA rats compared to that in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In general, if side effects occur, NSAIDs can be discontinued, or the patient can be treated with a proton pump inhibitor (PPI) or PG preparation [ 8 ]. However, we previously reported that the oral administration of rebamipide (RBM) enhanced the repair of indomethacin (IMC)-induced gastrointestinal injuries in adjuvant-induced arthritis (AA) rats, an animal model of RA [ 9 ]. Therefore, gastrointestinal injuries caused by NSAIDs may be treated with mucosal protective drugs such as RBM and teprenone (TEP) [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Labeled bacteriophages were embedded in cell membranes, and no transcytosis was seen for encapsulated phages, whereas unencapsulated phages crossed the cell membranes, indicating that liposomes increase the time that the phages are in the stomach. Lastly, a solid nanocrystal formulation of rebamipide has been developed for gastrointestinal bleeding . Solid nanocrystals were created with the bead mill method and were 30–190 nm.…”
Section: Stomach Drug Deliverymentioning
confidence: 99%